2021
DOI: 10.7554/elife.66984
|View full text |Cite
|
Sign up to set email alerts
|

Surface-associated antigen induces permeabilization of primary mouse B-cells and lysosome exocytosis facilitating antigen uptake and presentation to T-cells

Abstract: B-cell receptor (BCR)-mediated antigen internalization and presentation are essential for humoral memory immune responses. Antigen encountered by B-cells is often tightly associated with the surface of pathogens and/or antigen-presenting cells. Internalization of such antigens requires myosin-mediated traction forces and extracellular release of lysosomal enzymes, but the mechanism triggering lysosomal exocytosis is unknown. Here we show that BCR-mediated recognition of antigen tethered to beads, to planar lip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…This study shows that BCR activation by Fab’-PLB induces rapid recruitment of NMII to BCR activation sites, consistent with previous reports ( 40 , 43 ). Phosphorylated MLC is also recruited to the B-cell contact zone, suggesting that the recruited NMII is activated by BCR signaling.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This study shows that BCR activation by Fab’-PLB induces rapid recruitment of NMII to BCR activation sites, consistent with previous reports ( 40 , 43 ). Phosphorylated MLC is also recruited to the B-cell contact zone, suggesting that the recruited NMII is activated by BCR signaling.…”
Section: Discussionsupporting
confidence: 93%
“…NMII may negatively regulate BCR signaling by facilitating BCR endocytosis. NMII is critical for B-cells to pull Ag from Ag-presenting surfaces for endocytosis ( 40 , 42 , 43 , 55 ). BCR-mediated Ag endocytosis initiates Ag processing and presentation and also removes BCRs from surface signalosomes, potentially attenuating BCR proximal signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, B cell engagement with surface‐bound antigen seems also to trigger a lysosome‐mediated membrane resealing response. Maeda et al [ 81 ] have recently shown that BCR signalling following contact with surface‐bound antigen induced transient membrane permeabilization and lysosome exocytosis whose extent was proportional to BCR/antigen affinity. It seems that an ancient membrane repair response has been co‐opted by the immune system to aid antigen processing and presentation by B cells with high affinity for surface bound antigens.…”
Section: Adaptive Immunity: Generating Specific Antibodies and T Cellsmentioning
confidence: 99%